Friction and Shear Strength at the Nanowire–Substrate Interfaces - Gu Yi; Wang ZhongLin; Zhu Yong; Qin Qingquan (Nanoscale Research Letters, 2009)
Abstract The friction and shear strength of nanowire (NW)–substrate interfaces critically influences the electrical/mechanical performance and life time of NW-based nanodevices. Yet, very few reports on this subject are available in the literature because of the experimental challenges involved and, more specifically no studies have been reported to investigate the configuration of individual NW tip in contact with a substrate. In this letter, using a new experimental method, we report the friction measurement between a NW tip and a substrate for the first time. The measurement was based on NW buckling in situ inside a scanning electron microscope. The coefficients of friction between silver NW and gold substrate and between ZnO NW and gold substrate were found to be 0.09–0.12 and 0.10–0.15, respectively. The adhesion between a NW and the substrate modified the true contact area, which affected the interfacial shear strength. Continuum mechanics calculation found that interfacial shear strengths between silver NW and gold substrate and between ZnO NW and gold substrate were 134–139 MPa and 78.9–95.3 MPa, respectively. This method can be applied to measure friction parameters of other NW–substrate systems. Our results on interfacial friction and shear strength could have implication on the AFM three-point bending tests used for nanomechanical characterisation.